Primary Gliosarcoma with Extracranial Metastasis - Choi, Min Gyu; Lee, Jeong Ho; Lee, Min Seok; Suh, Sang Jun; Lee, Yoon Soo; Kang, Dong Gee (Brain tumor research and treatment, 2020)
A 69-year-old male presented with a week of worsening headache, mild dizziness and left side weakness, and the radiological work-up of his brain displayed an enhancing mass on the right frontal lobe. The tumor was totally resected. The patient was initially diagnosed with glioblastoma multiforme. His neurologic symptoms recovered after surgery. He underwent adjuvant radiotherapy with concurrent temozolomide. Approximately 7 months after surgery, the patient complained of epigastric pains. Abdominal CT scan showed multiple hepatic metastasis and multiple lymphadenopathy. Chest CT and Torso positron emission tomography-CT scans for additional metastasis study revealed multiple metastatic lesions in the right lung, left pleura, liver, lymph nodes, bones, and muscles. Percutaneous liver biopsy was performed, and associated pathology was consistent with sarcomatous component. After liver biopsy, brain tumor pathology was reviewed, which revealed typical gliomatous and sarcomatous components. The patient was therefore diagnosed with metastatic gliosarcoma. The patient was in a septic condition with aggravated pleural effusion. The patient died 9 months after the diagnosis of primary gliosarcoma.